FACIES MODELING OF SANDSTONE RESERVOIR X, UPPER GABUS FORMATION, KF FIELD, WEST NATUNA BASIN - Hanafi Nurhartanto, Faisal
KF field is a field of oil and gas producer located in Kakap PSC Block, West Natuna Basin. This field was discovered in 1985 and production commenced in December 1989 which reached its peak in November 1990 that produces 43,720 barrels of oil per day. Integrated study of further geology modeling (reservoir characterization) should conduct to fully understand characterization of the field. Reservoir modeling is one method which potential to apply in this field. This study conducted to model X sandstone reservoir of Upper Gabus Formation interval at KF Field. Several steps such as: well logs analysis, sediment types based on GR log pattern analysis, isochore mapping, reservoir geometry modeling, and facies modeling was carried in order to achieve the intended result. Well log data, 3D seismic data, checkshot data, well top and well bottom data, lithostratigraphy reports, internal company reports and studies ever conducted in the KF Field have been used in this study. There are four sandstone intervals that comprise X sandstone reservoir of Upper Gabus Formation, there are UG-7, UG-6, UG-5, and UG-4 interval. That four sandstone intervals are deposited in fluvial and fluvial-deltaic environments. Base on analysis of well logs on X sandstone reservoir interval, there are two sandstone facies, namely delta front facies/distal bar sands and fluvial channel sand facies. Reservoir facies modeling in this study using 3D seismic attribute RMS Amplitude. Selection is based on seismic attributes differences of seismic amplitudes between sandstones with mudstone facies so that identification becomes easier to done. Facies modeling shows deployment of facies and facies development of the sandstone interval from the oldest to the youngest sandstone intervals (UG-7 to UG-4). Facies modeling can be interpreted the spread of sandstone facies in KF Field is controlled by sedimentary environment development of fluvial-deltaic environment with deltaic progradation toward northwest.